(WITHDRAWN) TECHNICAL ELECTROSMOG (HIGH-FREQUENCY ELECTROMAGNETICFIELDS EMF) DAMAGES THE BRAIN, ESPECIALLY IN CHILDREN AND ADOLESCENTS - Doepp, Manfred (International Journal of Engineering Science Technologies, 2025)
(WITHDRAWN) The Author made the decision to withdraw the article.